TEACHERS’ PERSPECTIVES ON THE IMPLEMENTATION OF DIGITAL GAMIFICATION FOR VOCABULARY LEARNING: A THEMATIC ANALYSIS - Yeni Istiyani; Dwi Fita Heriyawati; Siti Mafulah (Universitas Negeri Semarang, 2026)
This study explores teachers’ voices toward the Implementation of Digital Gamification (DG) in the context of vocabulary mastery among young English as a Foreign Language ( EFL) Learners. Employing qualitative thematic analysis, this research delves into the experiences of teachers at a junior high school in Malang, based on data from semi-structured interviews. The findings on the benefits consistently highlighted two key themes: (1) enhanced vocabulary retention as perceived by teachers through enjoyable, repetitive exposure, and (2) enhanced learner motivation and engagement caused by interactive game-based activities. However, the implementation is impeded by several prominent challenges. The teachers’ voices pointed to significant technological barriers (unstable internet, device shortages), severe time constraints related to preparing and adapting game content, and issues managing young learners’ off-task behavior or excessive competitive stress. The study concludes that while teachers acknowledge the substantial pedagogical value of DG, successful integration requires systemic support to mitigate the identified technical and practical challenges. particularly in supporting students’ vocabulary development and addressing technological barriers in learning activities, and also solving the technological barriers in learning activity.